Regional Variations of Agricultural Productivity in Rice Cultivation in Thoubal District of Manipur - L. Sunil Singh , P. Robinson Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to examine the moderating role of organizational performance (OP) in the relationship between GHRM and social responsibility (SR) in the banking sector in Jordan. The population of the study consisted of all banks employees in Jordan, working at (808) bank branch; while the sample of the study included (500) employees selected using convenient random sampling method from the study population. For data collection, OP, GHRM and SR questionnaires were used. The results of the study showed that there is a statistically significant correlation (α=0.05) between the OP and SR; between the OP and GHRM; and between the SR and GHRM. The study also found that OP moderates the relationship between SR and GHRM among banks employees. In light of the results the study recommends the need for more consideration on GHRM practices in Jordanian banks as they may develop a positive reputation which may increase performance.